(untitled) (Journal of Computational Mathematics, 2000)
This paper deals with the error behaviour and the stability analysis of a class of linear multistep methods with the Lagrangian interpolation (LMLMs) as applied to the nonlinear delay differential equations (DDEs). It is showtn that a LMLM is generally stable with respect to the problem of class D_03c303b3, and a p-order linear multistep method together with a q-order Lagrangian interpolation leads to a D-convergent LMLM of order min p,q+1. 00a0